2011
DOI: 10.1007/s10804-010-9118-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Chronic Illness: the Case of Diabetes

Abstract: Globally, Type 2 Diabetes Mellitus (T2DM) is one of the most prevalent chronic illnesses. Managing T2DM is a major challenge now affecting the lives of around 200 million people. Even when medication, diet, and physical activity regimens are maintained, blood sugar levels might not be effectively controlled because stress triggers the release of sugar into the blood. This makes the management of stress an important adjunct to the treatment of T2DM. Stress includes both life stress, the major issues that people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 62 publications
1
32
0
3
Order By: Relevance
“…This indication that higher HbA1c measures are related to greater levels of diabetes-related distress is consistent with previous research. Several studies reported that life challenges associated with diabetes may cause additional stress for individuals with T2DM, resulting in a negative impact on psychological well-being and metabolic control [3,10]. Karlsen and colleagues, for example, found adults with both type 1 diabetes and T2DM experienced difficulty managing their diabetes during the winter months when diets included more enriched foods (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indication that higher HbA1c measures are related to greater levels of diabetes-related distress is consistent with previous research. Several studies reported that life challenges associated with diabetes may cause additional stress for individuals with T2DM, resulting in a negative impact on psychological well-being and metabolic control [3,10]. Karlsen and colleagues, for example, found adults with both type 1 diabetes and T2DM experienced difficulty managing their diabetes during the winter months when diets included more enriched foods (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, significant psychosocial challenges associated with diabetes which are often unaddressed and warrant discussion. As the literature attests, diagnosis of T2DM can lead to emotional distress regarding lifestyle changes, adjustments with relationships, and social networks [3]. Upon receiving a T2DM diagnosis, younger adult patients (under 65 years old) were more likely to experience anxiety as a result of their diagnosis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the relationship between stress and weak blood sugar control in those with diabetes. They have also investigated the effect of different stress management strategies on blood sugar levels (T. Morris, Moore, & F. Morris, 2011).…”
Section: Importance Of the Problemmentioning
confidence: 99%
“…Evidence suggests that life stress can adversely affect blood glucose control in patients with type 2 diabetes (Morris et al, 2011), perhaps by depleting the psychological resources needed for effective diabetes self-management (Hagger et al, 2009) or by triggering the release of hormones that contribute to elevated blood glucose (Surwit and Schneider, 1993). Yet the association between stress and blood glucose control exhibits considerable individual variability (Riazi et al, 2004), and this variability may be due, in part, to individual differences in the degree to which stress arouses emotional distress (Soo and Lam, 2009).…”
Section: Discussionmentioning
confidence: 99%